Degradability of Rumen-Protected Soybean Meal with Different Temperatures and Heating Times in Bali Cattle - Wulandari Wulandari; Rinanti Eka Aldis; Dananto Ramadhan; Wulanningtyas Wulanningtyas; Andriyani Astuti; Adiarto Adiarto; Lies Mira Yusiati; Cuk Tri Noviandi; Budi Prasetyo Widyobroto; Ali Agus (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
The goal of this study was to ascertain the impact of soybean meal's temperature and heating duration as undegraded protein (UDP) on Bali cattle's dry matter (DM) and organic matter (OM) degradation kinetics. Soybean meal is a feed ingredient with high protein content, which is about 48%, and is rapidly degraded in the rumen. In this investigation, a factorial design was employed with the first factor being temperature (60, 80, 100, and 120°C), and the second factor being heating time (10, 20, 30, and 40 min). Protected soybean meal was tested for degradation using the in sacco technique on the rumen of fistulous Bali cattle. A sample of 5.0 g was put into a nylon bag and then for 0, 2, 4, 8, 16, 24, and 48 h in the rumen, then analyzed for feed residues for DM and OM. The results showed that soybean meal protected by the heating method could reduce the degradation of DM and OM in the rumen (p<0.05). Heating at 120°C for 40 min showed the lowest DM and OM degradations in this study.